The association of obesity and severe dengue: possible pathophysiological mechanisms. Issue 1 (July 2020) - Gallagher, Peter; Chan, Kuan Rong; Rivino, Laura; Yacoub, Sophie
Abstract: Dengue virus (DENV) is a medically important flavivirus and the aetiological agent of Dengue, a normally self-resolving febrile illness that, in some individuals, can progress into Severe Dengue (SD), a life-threatening disorder that manifests as organ impairment, bleeding and shock. Many different risk factors have been associated with the development of SD, one of which is obesity. In many countries where DENV is endemic, obesity is becoming more prevalent, therefore SD is becoming an increased public health concern. However, there is a paucity of research on the mechanistic links between obesity and SD. This is a narrative review based on original research and reviews sourced from PubMed and Google Scholar. Four key areas could possibly explain how obesity can promote viral pathogenesis. Firstly, obesity downregulates AMP-Protein Kinase (AMPK), which leads to an accumulation of lipids in the endoplasmic reticulum (ER) that facilitates viral replication. Secondly, the long-term production of pro-inflammatory adipokines found in obese individuals can cause endothelial and platelet dysfunction and can facilitate SD. Thirdly, obesity could also cause endothelial dysfunction in addition to chronic inflammation, through the production of reactive oxygen species (ROS) and possible damage to the glycocalyx found in the endothelium. Finally, obesity has several effects on immunomodulation that reduces NK cell function, B and T cell response and increased pre-disposition to stronger pro-inflammatory cytokine responses after viral infection. Together, these effects can lead to greater viral proliferation and greater tissue damage both of which could contribute to SD. The four mechanisms outlined in this review can be taken as reference starting points for investigating the link between obesity and SD, and to discover potential therapeutic strategies that can potentially reduce disease severity.